Off-chemotherapy dermatitis. A new entity? - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
The Authors report 11 cases of a characteristic disorder arising in leukemic children by one month from withdrawing the chemotherapy. The disorder is characterized by eczema-like lesions that spontaneously regress within 3 months. It is not caused by infectious agents and is not related with atopy. However, it is reminiscent of seborrheic dermatitis. The Authors propose the name "off-chemotherapy dermatitis" for this disorder, that is not reported in the relevant literature.